Evaluation of the Iowa State Residential Substance Abuse Treatment Program, 1998-1999 - Cadoret, Remi J. ([Verlag nicht ermittelbar], 2003)
This study sought (1) to set up a system to evaluate the operations and effectiveness of The Other Way (TOW) residential substance abuse treatment program at the Clarinda Correctional Facility in Clarinda, Iowa, and (2) to assist program staff in developing and implementing intake, discharge, and follow-up instruments and evaluation protocols to document inmate characteristics and changes over time related to substance use/abuse, mental health, social functioning, and criminal behavior and attitudes. Inmates are referred to this program if they have an identified need for residential-level substance abuse treatment and are within 12 months of release consideration. TOW is a voluntary, six-month long program that works with inmates to identify the causes of their addictive behaviors and encourage changes in unacceptable behaviors and criminal thinking. The sample for this study consists of adult male inmates at the Clarinda Correctional Facility between January 1998 and March 1999. The first point of data collection was the intake assessment. At intake, each subject completed an intake packet consisting of several instruments that measured variables relevant to TOW program goals. Each inmate was also given an Addiction Severity Index (ASI) interview by a counselor at intake. Upon discharge from the program, each subject completed a discharge packet, which contained instruments slightly different from those in the intake packet. Instruments were chosen for reliability and validity, ease of administration, potential for dual clinical and evaluation use, and whether they duplicated any existing efforts. Versions of the following instruments were included in both the intake and discharge packets: the Colorado Cognitive Assessment Questionnaire, Circumstances, Motivation, and Readiness (CMR) Scales for Substance Abuse Treatment, the Social Provisions Scale (SPS), the Self-Help Questionnaire, and the STEPS Questionnaire. A consumer satisfaction survey was also administered at the discharge interview. Variables obtained from answers to the ASI include gender, living situation, date of birth, race, religion, length of incarceration, medical status, education and employment history, sources of financial support, family/social relationships including abuse history, psychiatric status, drug and alcohol use including kinds of drugs used, length of use, age at first use, and frequency of use for each drug, personal problems caused by drug use, drug treatment history, legal history, and family history of drug, alcohol, and psychological problems. Intake assessment variables included are related to social attitudes, and include variables on life goals and the subjects' own views of their achievability, how subjects thought their friends viewed them, how wrong subjects thought certain illegal acts were, and criminal acts by the subjects' friends in the past six months. Discharge packet variables include the same variables on social attitudes as the intake packet as well as variables obtained from answers to the SPS relating to the amount of social support subjects felt they had, past involvement with self-help groups, and life attitudes related to drug/alcohol use.